EFL coursebook innovation: the dynamics of L2 maturity, student engagement, and cognitive development - Murphy, Robert S. (2019)
This thesis documents the dynamically changing efficacy of an EFL coursebook series that has been evolving in various ways since 2008, via action research methodology. The Optimal Levels EFL coursebook series was specifically written for the Japanese EFL context―but with the strong intent of raising students’ cognitive maturity along with their L2 competence. Because of this non-conventional attention to maturity in combination with L2 learning, the ensuing research of Optimal Levels’ efficacy required a non-conventional evaluation system. This thesis therefore serves to document the evolution of the series (with all of its theoretical underpinnings), and also document the evolution of the various evaluation systems that were developed for this somewhat convoluted project. To accomplish these goals, the research not only follows the growth of Japanese EFL students’ L2 competence, but it also follows the changes of students’ feelings of ownership of the L2, their changes in engagement with provided L2 tasks, their changes in metacognitive realizations regarding learning/teaching, and also their L2 maturation rate changes under several different conditions. The efficacy of the original Optimal Levels (OL1) was compared to that of New Optimal Levels (OL2). Both books have a significant amount of overlap in their pedagogical approach and learning tasks. From a historical perspective, OL1 was developed as an integral part of my MA thesis while OL2 was developed as an integral part of this doctoral thesis. The design of OL2 evolved along with this study’s findings. Therefore, in the second half of the thesis I will discuss the developments that led to OL2 Revised (an updated version of OL2 that I also piloted with students for this project). In broad strokes, it can be said that the original design of OL1 (and then OL2 and OL2-R) stem from developments in Applied Linguistics, Cognitive Psychology and Educational Neuroscience. Quantitative analysis (SPSS-based statistics and Lectical Analysis) was used to measure the difference in the growth patterns of two groups of university students; the results of the OL1 group were compared with the results of the OL2 group. Lectical Analysis data showed that the OL2 group outpaced the OL1 group by an 8x growth rate of demonstrable L2 complexity--with a single 15-week semester of teaching. Qualitative analysis (student-based focus group interviews, questionnaires, and evaluation essays from university students) was used to deduce the specifics behind the performance gap between the two groups. The data revealed that OL2 raised metacognitive awareness and feelings of L2 ownership in the students; participants in the OL2 group were more willing to discuss the hows and whys of their L2 growth, while the OL1 group focused more on what they did in class, which is considerably less of a cognitive challenge for students in this age group. The compilation of data from the variety of evolving studies suggested significant connections across: (a) cyclically designed deep-thinking tasks, (b) metacognitive nurturing in the L2 classroom, and (c) rapid L2 maturation rates. The implication is that in the EFL classroom, a purely “pragmatic” focus on linguistic development can be ironically counterproductive in raising the maturation rates of EFL students’ L2 competence. Two sets of tenets for classroom teachers and material developers were developed as a result of these studies; the tenets are a culmination of all of the major insights that were acquired across this six-year project. For the finale of the thesis, the tenets were used to upgrade the design of OL2-R into what will become OL3. In this way, the ending of the thesis ties the knot between: (1) theoretical understandings of the amassed data and (2) practical applications of the amassed data from this action research project.